Problems in calculating gas-make in the operating panels in view of geomechanical and gas-dynamic processes, and method to resolve them - Elena Shubina; Viktor Lukyanov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the research is caused by the complexity in predicting gas-dynamic processes and their influence on gas-make in the operating panels when mining gas bearing coal deposits; as well as the need to utilise mining equipment in accordance with its specified capability, except the equipment downtime due to the gas factor at coal mining. The aim of the research is to study the extraction of in-situ coal mass in small dip angles; to form gas-dynamic events and to identify the problems in calculating gas-make when mining coal deposits in order to ensure safety standards at coal and methane production on industrial scale. The authors have studied geomechanical and gasodynamic processes which occur while mining at development of gas-bearing coal fields. The paper considers the problem issues of calculating gas release into an extraction district. The paper introduces the methods for decreasing natural gas content by the mining start relating to a complex approach to the scheme of exploration wells distribution at the stage of exploration works planning. The authors proposed to use these wells for different kinds of coal bed degasification and methane production in industrial scale. Application of the methods allows excluding the possibility of unexpected massive gas-make in mining heading and ensures safety regulations for mining in coal mines. Results. Pre-production gas drainage of working and adjacent seams using exploratory boreholes prior to commencing mining of the deposit via underground method, will significantly reduce gas-make into development headings and production area, ensuring safe coal mining and gas extraction. Use of exploratory boreholes for gas drainage reduces the costs of implementing measures to reduce the natural gas content; it allows automated methane extraction on industrial scale.